'Marriage of convenience' or a 'match made in heaven': lawyers and social workers working with asylum seekers - Fiske, Lucy; Kenny, M. (2004)
Asylum seekers face many hurdles during the process of refugee status determination, particularly if they have experienced some form of trauma. By preparing cases as a team, lawyers and social workers can reduce the stress for asylum seekers while at the same time improve the quality of information made available to decision makers within the refugee determination process. This article presents a model which utilises the knowledge and skills that lawyers and social workers are able to bring to working with asylum seekers and assists asylum seekers to present a comprehensive case with a focus both on supporting their credibility and maximizing their ability to actively engage in the process.